INTERPRETATION OF THE CONCEPT OF SPIRITUAL CULTURE BY SCIENTISTS - Quchqorova N. M.; Jurayeva N. A. (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the concept of spiritual culture, our national values, the views and opinions of scholars who have conducted research on the development of spiritual culture of modern teachers, the role of spirituality and culture in the development of our society.